CD20 expression is closely associated with Epstein–Barr virus infection and an inferior survival in nodular sclerosis classical Hodgkin lymphoma - Zhao, Xia; Ma, Yushuo; Bian, Haiyan; Liu, Zhihe (Frontiers in Oncology, 2022)
Background Nodular sclerosis classical Hodgkin lymphoma (NSCHL) is a rare disease in which Epstein–Barr virus (EBV) and CD20 can be detected. The clinical significance of EBV infection, CD20 expression and their relationship are still unclear in NSCHL presently. The aim of this research was to systematically explore the clinical significance of EBV infection, expression of CD20 and their relationship in NSCHL. Methods 109 NSCHL patients diagnosed in Qingdao University’s Affiliated Hospital were chosen from January 2010 to July 2019, and the clinical and survival data of all patients were collected retrospectively. Results Among 109 patients, 33 patients were assigned to the group of EBV-positives, following the results of the EBV-encoded RNA (EBER1). Compared with EBV-negative group patients, those in the group of EBV-positive were older (P=0.004) and their β2-microglobulin (β2-MG) levels were higher (P=0.006). The CD20 positivity rate in the group of EBV-positive was substantially higher than that in the EBV-negative group (54.5% vs 27.6%, P=0.007). Among 109 patients, EBV+ and CD20+ double positive patients acquired the least overall survival (OS), and patients with EBV- and CD20- double negative had the best OS (P < 0.001). Although old age, gender, EBV infection and CD20 positive were the risk factors for OS in NSCHL, multivariate analysis showed that CD20 positivity was the only characteristic that showed to be an independent risk factor for OS in NSCHL patients. Conclusion CD20 was found to be strongly expressed in NSCHL patients who had been infected with EBV, and it was found to be an independent risk factor for NSCHL patients’ survival.